Oxygen isotopic fractionation during dissolved oxygen consumption in the bottom layer of the Ulleung Basin, East/Japan Sea - Kim, Yeseul; Kang, Dong-Jin (Frontiers in Marine Science, 2024)
The interpretation of decline in dissolved oxygen (DO) in the oxygenated bottom water of the Ulleung Basin (UB), southwest of the East/Japan Sea has been challenging because of the integrated influence of various DO-consuming processes. Therefore, the stable oxygen isotopic fractionation of DO was investigated to enhance our understanding of the distinct DO consumption observed in the bottom layers of the center of the UB. We explored the relationship between DO and its oxygen isotope composition (δ18ODO) using data collected at a station located in the center of the UB in 2020, 2021, and 2022. An unforeseen decrease in δ18ODO in the bottom layer (> 1800 m) where DO was depleted was discovered. The overall DO consumption in the mesopelagic water layer (300–1000 m), primarily attributed to water column respiration, exhibited an isotopic fractionation factor (α) with 0.985 ± 0.001 in the δ18ODO/[O2] relationship. The consumptive isotope fractionation factor in the bottom waters near the sediments (approximately 2146 m) showed a value slightly higher (0.988 ± 0.002) than that in the mesopelagic water layer. This isotopic signature is likely due to a smaller fractionation in the bottom waters relative to the mesopelagic water. The isotopic evidence suggests the involvement of mineral oxidation associated with excess dissolved Mn and Fe in the bottom waters because mineral oxidation exhibits a smaller fractionation effect than respiration. Our study demonstrates that DO depletion results from multiple consumption processes, including respiration, mineral oxidation, and diffusive transport, and the isotopic behavior provides evidence that mineral oxidation significantly influences DO consumption.